AN EMPIRICAL STUDY ON CUSTOMER RETENTION IN HEALTH INSURANCE SECTOR IN ODISHA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The aim of this research is to investigate the  factors affecting customer retention in the  sector of health insurance. Five factors were  taken in this research based on past studies  in insurance sector; they are Insurance plans,  Premiums, Services delivered, Employee  Empathy and Reliability. At the beginning,  T-test was conducted and according to the  results obtained all the five factors mentioned  were found to be significant. Then in order to  cross verify the results obtained from T-test,  multiple regressions was conducted taking  Customer Retention as the dependent variable  and the other five factors; Insurance plans,  Premiums, Services delivered, Employee  Empathy and Reliability as the independent  variables. In multiple regression analysis,  all the factors were found significant except  Employee Empathy which was found to be  of no significance. According to the results  obtained in multiple regression analysis the  null hypothesis which stated that “Employee  Empathy has no role to play in Customer  Retention” was accepted where as the other null  hypotheses were rejected. So, in this study the  Insurance plans, Premiums, Services delivered  and Reliability emerged as the factors that affect  the customer retention in health insurance  sector.
Keywords: Customer Retention; Health insurance; insurance plans; Premiums; Services delivered; Employee Empathy,; Reliability; T-test; multiple regression